Coupling Effect of Operating Conditions on Performance of SOFC-GT with Anode Exhaust Gas Recirculation - Suthin Pholboorn; Yaneeporn Patcharavorachot (My University, 2023)
This work proposed a study on a hybrid system of solid oxide fuel cell (SOFC) and gas turbine (GT) with anode exhaust gas recirculation. A pre-reformer of methane was suggested to reduce a complete reforming reaction in a SOFC stack. Thus, the pre-reforming percentage as an important parameter was examined, coupling with main operating conditions that include steam to carbon ratio (S/C), SOFC temperature, SOFC pressure, anode recirculation ratio (AR), fuel utilization (Uf). Thermodynamics calculation of this system was carried out by using Aspen Plus simulator. The investigation results revealed that increasing pre-reforming percentage reduce both efficiencies of SOFC and hybrid system. This is in turn that a low level of methane pre-reforming is sufficient to operate in SOFC-GT system with anode exhaust gas recirculation. In addition, the results revealed that the maximum system efficiency of 94.65% can be obtained at 10% pre-reforming, S/C of 2.0, SOFC temperature of 1173 K, SOFC pressure of 7 bar, AR of 0.3 and Uf of 0.9.
Keywords: Advancements in Solid Oxide Fuel Cells; Fuel Cells and Related Materials; Electrocatalysts for Energy Conversion